Liner-free carbon fiber fully wound composite material gas cylinder and preparation method thereof
By setting a graphene modified layer and a plasma deposition layer between the winding layers of the cylinder center body, the gas leakage problem that the lineless composite gas cylinder may occur under low temperature conditions is solved, and better anti-leakage effect and buffering performance are achieved.
Patent Information
- Application Number
- CN202411093239.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-08-09
AI Technical Summary
The gas leak problem may occur in low temperature conditions in the unlined composite gas cylinder, and it is necessary to improve the leakage prevention effect without affecting the load-bearing capacity.
A graphene modified layer and a plasma deposition layer are arranged between the two winding layers of the center body of the gas cylinder. The graphene modified layer is arranged in a directional manner through the surface adsorption of magnetic nanoparticles and using an external magnetic field to form a uniformly covered layer structure, thereby improving the density and bonding of the plasma deposition layer.
It realizes the anti-leakage effect of the fully wound composite gas cylinder without lined carbon fiber without affecting the bearing capacity of the composite material, and enhances the buffering performance of the gas cylinder.
Smart Images

Figure CN118881920B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a liner-free carbon fiber fully-wound composite material gas cylinder and a preparation method thereof, belonging to the technical field of high-pressure containers. Background Art
[0002] Linerless composite gas cylinders (i.e., Type V pressure vessels) have always been the goal of designing carbon fiber composite pressure vessels. Traditionally, pressure vessels of types I to IV all use a certain percentage of metal materials, and at least use metal liners to separate the stored gas or liquid from the composite material (such as Type IV pressure vessels). Linerless composite gas cylinders, as a type of pressure vessel, have significant advantages in weight and cost compared to metal tanks. Eliminating the metal lining layer can greatly reduce the weight of composite gas cylinders. Studies have shown that the use of composite gas cylinders in carrier tanks can reduce the weight of the structure by 20% to 40%. It can not only reduce the cost of the carrier, but also increase the payload carrying capacity.
[0003] In addition to considering the load-bearing capacity of composite materials, the use of all-composite materials in unlined composite gas cylinders also needs to fully consider the possibility of cryogenic fluid leakage. Therefore, the elimination of the metal lining layer requires that the composite structure layer be able to withstand the internal high-pressure load during service, and how to prevent leakage has become a research focus in this field.
[0004] It should be noted that the above content belongs to the scope of knowledge of technology and does not necessarily constitute prior art. Summary of the invention
[0005] In order to solve the above problems, the present application proposes a linerless carbon fiber fully wound composite material gas cylinder and a preparation method thereof, wherein a graphene modified layer and a plasma deposition layer are arranged between the two winding layers of the central body of the gas cylinder, and the graphene modified layer is a layer structure formed by graphene with magnetic nanoparticles adsorbed on the surface. According to the magnetic properties of the magnetic nanoparticles, the magnetically modified graphene is oriented on the surface of the carbon fiber winding layer to form a flat and evenly covered graphene modified layer, so that the plasma deposition layer is easier to deposit and the deposition is more dense, and the bonding degree between the graphene modified layer and the plasma deposition layer is better. Since graphene itself has excellent flexibility and strength, it can ensure that the linerless carbon fiber fully wound composite material gas cylinder has better anti-leakage effect without affecting the carrying capacity of the composite material.
[0006] The technical solution of this application is as follows:
[0007] According to one aspect of the present application, there is provided a liner-free carbon fiber fully wound composite gas cylinder, comprising a central body, wherein the central body comprises a multilayer structure and a gas storage cavity surrounded by the multilayer structure, wherein the multilayer structure comprises:
[0008] A plurality of composite carbon fiber winding layers, which are formed by winding carbon fiber composite materials;
[0009] Wherein, at least one adjacent composite carbon fiber winding layer comprises a first winding layer and a second winding layer, and a first graphene modified layer and a plasma deposition layer are sequentially arranged from the outer side of the first winding layer to the inner side of the second winding layer;
[0010] The first graphene modified layer is a layer structure formed by graphene with magnetic nanoparticles adsorbed on the surface.
[0011] Through the above technical solution, a graphene modified layer is arranged between the two winding layers of the central body of the gas cylinder. The graphene modified layer uses graphene with magnetic nanoparticles adsorbed on the surface, so that the surface of the graphene is magnetically modified, and the magnetically modified graphene is oriented and arranged on the surface of the carbon fiber winding layer by an external magnetic field, forming a flat and evenly covered graphene modified layer, thereby making the plasma deposition layer easier to deposit and more dense, and the bonding degree between the graphene modified layer and the plasma deposition layer is better. The magnetic nanoparticles used for the graphene guided modification can also form a chemical bond with the plasma deposition layer during the plasma deposition process, thereby improving the bonding effect between the graphene modified layer and the plasma deposition layer, and improving the bonding effect between the winding layer, the graphene modified layer and the deposition layer.
[0012] Optionally, the carbon fiber composite material comprises carbon fiber and resin matrix prepreg;
[0013] The mass ratio of the graphene to the magnetic nanoparticles is 1:(0.1-2);
[0014] The graphene and the magnetic nanoparticles form a first mixed system, and the mass ratio of the first mixed system to the resin matrix prepreg is (0.1-5):100.
[0015] Further, the mass ratio of the graphene to the magnetic nanoparticles is 1:(0.5-1.8);
[0016] The graphene and the magnetic nanoparticles form a first mixed system, and the mass ratio of the first mixed system to the resin matrix prepreg is (0.5-4):100.
[0017] Furthermore, the mass ratio of the graphene to the magnetic nanoparticles is 1:(0.5-1.5);
[0018] The graphene and the magnetic nanoparticles form a first mixed system, and the mass ratio of the first mixed system to the resin matrix prepreg is (0.5-3):100.
[0019] Optionally, the liner-free carbon fiber fully wound composite material gas cylinder further includes a second graphene modified layer disposed between the plasma deposited layer and the second wound layer;
[0020] The second graphene modified layer is a layer structure formed by graphene with magnetic nanoparticles adsorbed on the surface.
[0021] Optionally, the magnetic nanoparticles are Fe3O4 magnetic nanoparticles.
[0022] Optionally, the thickness ratio of the plasma deposited layer to the first winding layer is (0.1-2): 1. Further, the thickness ratio of the plasma deposited layer to the first winding layer is (0.3-1.8): 1. Further, the thickness ratio of the plasma deposited layer to the first winding layer is (0.5-1.5): 1.
[0023] Optionally, the precursor material of the plasma deposition layer includes metal materials, ceramic materials and metal organics.
[0024] Optionally, the metal material includes at least one of Al, Fe, Ti, Co, Ni, Cu, Ru, Pd, Ag, Ta, Ir, Pt and alloys thereof;
[0025] The ceramic material includes at least one of titanium nitride, zirconium nitride, zirconium carbide, zirconium carbonitride, titanium oxide, and copper aluminum oxide;
[0026] The metal organic compound includes at least one compound selected from the group consisting of a metal alkyl compound, a metal cyclopentadienyl compound, a metal amide compound and a metal ether compound.
[0027] According to another aspect of the present application, a method for preparing a liner-free carbon fiber fully wound composite gas cylinder is provided, the preparation method comprising the following steps:
[0028] S1. A first mixed system: mixing graphene and magnetic nanoparticles so that the magnetic nanoparticles are adsorbed on the surface of the graphene to obtain the first mixed system;
[0029] S2. Resin matrix prepreg: The first mixed system obtained in S1 is added to the resin matrix and mixed evenly to obtain the resin matrix prepreg;
[0030] S3. Carbon fiber composite material: several carbon fibers are arranged in parallel to form a carbon fiber bundle, the carbon fiber bundle is pre-impregnated into the resin matrix prepreg obtained in S2, and then the pre-impregnated carbon fiber bundle is passed through a magnetic field, under the action of the magnetic field, the graphene adsorbed with magnetic nanoparticles in the resin matrix prepreg pre-impregnated with the carbon fiber bundle is uniformly arranged on the upper and lower sides of the carbon fiber bundle, and graphene modified layers are respectively formed on the upper and lower sides of the carbon fiber bundle, and finally a carbon fiber composite material is obtained;
[0031] S4. Central body: Winding the carbon fiber composite material obtained in S3 to first form a first winding layer, spraying a plasma deposition layer on the outer surface of the first winding layer, and winding a second winding layer on the outer surface of the plasma deposition layer to obtain the central body.
[0032] Through the above technical scheme, the graphene modified by magnetic nanoparticles is added to the prepared resin matrix prepreg, and after the carbon fiber forms the carbon fiber bundle prepreg with the resin matrix prepreg, a magnetic field is passed through, and under the action of the magnetic field, the graphene modified by magnetic nanoparticles is evenly arranged on the upper and lower sides of the carbon fiber bundle, forming a flat and evenly covered graphene modified layer, so that the sprayed plasma deposition layer is easier to deposit and the deposition is more dense, and the bonding degree between the graphene modified layer and the plasma deposition layer is better. The magnetic nanoparticles used for the directional modification of graphene can also form a chemical bond with the plasma deposition layer during the plasma deposition process, thereby improving the bonding effect of the graphene modified layer and the plasma deposition layer, and improving the bonding effect of the winding layer, the graphene modified layer and the deposition layer. Because graphene itself has excellent flexibility and strength, it can ensure that the non-lined carbon fiber fully wound composite gas cylinder has a better anti-leakage effect without affecting the carrying capacity of the composite material, and has better buffering performance.
[0033] Optionally, in S1, the magnetic nanoparticles are Fe3O4 magnetic nanoparticles, and the mass ratio of the graphene to the magnetic nanoparticles is 1:(0.1-2).
[0034] Further, the mass ratio of the graphene to the magnetic nanoparticles is 1:(0.5-1.8);
[0035] Furthermore, the mass ratio of the graphene to the magnetic nanoparticles is 1:(0.5-1.5).
[0036] Optionally, in S2, the mass ratio of the first mixing system to the resin matrix prepreg is (0.1-5):100.
[0037] Furthermore, the graphene and the magnetic nanoparticles form a first mixed system, and the mass ratio of the first mixed system to the resin matrix prepreg is (0.5-4):100.
[0038] Furthermore, the graphene and the magnetic nanoparticles form a first mixed system, and the mass ratio of the first mixed system to the resin matrix prepreg is (0.5-3):100.
[0039] Optionally, in S3, the pre-impregnation temperature is 50°C-200°C, and the pre-impregnation time is 1-5min;
[0040] The magnetic field is a double-layer magnetic field, which is respectively arranged on the upper and lower sides of the path of the carbon fiber bundle, and the speed of the carbon fiber bundle passing through the magnetic field is 1-2m / min.
[0041] Optionally, the spraying temperature of the plasma deposited layer is not lower than the temperature of the first winding layer, and is not higher than the molten state temperature of the resin matrix in the carbon fiber composite material.
[0042] Optionally, the thickness ratio of the plasma deposited layer to the first winding layer is (0.1-2): 1. Further, the thickness ratio of the plasma deposited layer to the first winding layer is (0.3-1.8): 1. Further, the thickness ratio of the plasma deposited layer to the first winding layer is (0.5-1.5): 1.
[0043] Optionally, the precursor material of the plasma deposition layer includes metal materials, ceramic materials and metal organics.
[0044] Optionally, the metal material includes at least one of Al, Fe, Ti, Co, Ni, Cu, Ru, Pd, Ag, Ta, Ir, Pt and alloys thereof;
[0045] The ceramic material includes at least one of titanium nitride, zirconium nitride, zirconium carbide, zirconium carbonitride, titanium oxide, and copper aluminum oxide;
[0046] The metal organic compound includes at least one compound selected from the group consisting of a metal alkyl compound, a metal cyclopentadienyl compound, a metal amide compound and a metal ether compound.
[0047] It should be noted that the resin matrix used in the "resin matrix prepreg" in this application can be a thermosetting resin matrix or a thermoplastic resin matrix. The resin in the thermosetting resin matrix, such as epoxy resin, phenolic resin, benzoxazine, bismaleimide, polyimide; the thermoplastic resin matrix, such as mainly polysulfone, polyphenylene sulfide, polyether sulfone and other resins, is not limited here.
[0048] The beneficial effects of this application include but are not limited to:
[0049] 1. The non-lined carbon fiber fully wound composite gas cylinder provided by the present application has a graphene modified layer arranged between the two winding layers of the central body of the gas cylinder. The graphene modified layer uses graphene with magnetic nanoparticles adsorbed on the surface, so that the surface of the graphene is magnetically modified, and the magnetically modified graphene is oriented on the surface of the carbon fiber winding layer by an external magnetic field to form a flat and evenly covered graphene modified layer, thereby making the plasma deposition layer easier to deposit and more dense, and the bonding degree between the graphene modified layer and the plasma deposition layer is better. The magnetic nanoparticles used for graphene guided modification can also form a chemical bond with the plasma deposition layer during the plasma deposition process, thereby improving the bonding effect of the graphene modified layer and the plasma deposition layer, and improving the bonding effect of the winding layer, the graphene modified layer and the deposition layer. Since graphene itself has excellent flexibility and strength, it can ensure that the non-lined carbon fiber fully wound composite gas cylinder has a better anti-leakage effect without affecting the carrying capacity of the composite material.
[0050] 2. The preparation method of the non-lined carbon fiber fully wound composite gas cylinder provided by the present application, in which the graphene modified by magnetic nanoparticles is added to the prepared resin matrix prepreg, and after the carbon fiber forms a carbon fiber bundle pre-impregnated with the resin matrix prepreg, a magnetic field is passed through, and under the action of the magnetic field, the graphene modified by magnetic nanoparticles is evenly arranged on the upper and lower sides of the carbon fiber bundle, forming a flat and evenly covered graphene modified layer, thereby making the sprayed plasma deposition layer easier to deposit and deposit more densely, and the bonding degree between the graphene modified layer and the plasma deposition layer is better. The magnetic nanoparticles used for graphene-guided modification can also form a chemical bond with the plasma deposition layer during the plasma deposition process, thereby improving the bonding effect of the graphene modified layer and the plasma deposition layer, and improving the bonding effect of the winding layer, the graphene modified layer and the plasma deposition layer. Because graphene itself has excellent flexibility and strength, it can ensure that the non-lined carbon fiber fully wound composite gas cylinder has a better anti-leakage effect without affecting the carrying capacity of the composite material, and has better buffering performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0052] Figure 1 This is a schematic diagram of the structure of a liner-free carbon fiber fully-wound composite material gas cylinder involved in an embodiment of the present application;
[0053] Figure 2 This is a schematic diagram of the central body structure of a liner-free carbon fiber fully-wrap composite material gas cylinder involved in an embodiment of the present application;
[0054] Figure 3 for Figure 2 An enlarged schematic diagram of A in FIG.
[0055] List of parts and reference numerals:
[0056] 1. Unlined carbon fiber fully wound composite gas cylinder; 11. Gas storage chamber; 2. Center body; 3. Composite carbon fiber winding layer; 31. First winding layer; 32. Second winding layer; 33. First graphene modified layer; 34. Second graphene modified layer; 35. Plasma deposition layer. DETAILED DESCRIPTION
[0057] In order to more clearly understand the above-mentioned purposes, features and advantages of the present application, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0058] In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application may also be implemented in other ways different from those described herein. Therefore, the scope of protection of the present application is not limited to the specific embodiments disclosed below.
[0059] In addition, in the description of the present application, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0060] In the present application, unless otherwise clearly specified and limited, a first feature "above" or "below" a second feature may be that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in an appropriate manner in any one or more embodiments or examples.
[0061] The embodiment of the present application discloses a non-liner carbon fiber fully wound composite gas cylinder, such as Figure 1-3 As shown, the liner-free carbon fiber fully wound composite gas cylinder 1 includes a central body 2, and the central body 2 includes a multilayer structure and a gas storage cavity 11 surrounded by the multilayer structure; the multilayer structure includes: a plurality of composite carbon fiber winding layers 3 formed by winding carbon fiber composite materials; wherein, at least one adjacent composite carbon fiber winding layer 3 includes a first winding layer 31 and a second winding layer 32, and a first graphene modified layer 33 and a plasma deposition layer 35 are sequentially arranged from the outer side surface of the first winding layer 31 to the inner side surface of the second winding layer 32; the first graphene modified layer 33 is a layer structure formed by graphene with magnetic nanoparticles adsorbed on the surface.
[0062] It can be understood by those skilled in the art that the outer side and inner side of the winding layer described in the embodiment of the present application, such as the outer side of the first winding layer 31 and the inner side of the second winding layer 32, refer to the side of the winding layer close to the air storage chamber 11 of the central body 2 being defined as the inner side, and the other side being defined as the outer side. In the embodiment of the present application, at least one adjacent composite carbon fiber winding layer 3 includes a first winding layer 31 and a second winding layer 32, and a first graphene modified layer 33 and a plasma deposition layer 34 are sequentially arranged from the outer side of the first winding layer 31 to the inner side of the second winding layer 32. Since the central body 2 is a multi-layer structure, the structure between the above winding layers (graphene modified layer and plasma deposition layer) can be arranged between any two adjacent winding layers, or between two or more adjacent winding layers.
[0063] Through the above technical solution, a graphene modified layer is arranged between the two winding layers of the central body 2 of the gas cylinder. The graphene modified layer uses graphene with magnetic nanoparticles adsorbed on the surface, so that the surface of the graphene is magnetically modified, and the magnetically modified graphene is oriented on the surface of the carbon fiber winding layer by using an external magnetic field to form a graphene modified layer with good flatness and uniform coverage, thereby making the plasma deposition layer easier to deposit and deposit more densely, while better controlling the thickness and flatness of the plasma deposition layer, and the bonding degree between the graphene modified layer and the plasma deposition layer is better. The magnetic nanoparticles used for the graphene guided modification can also form a chemical bond with the plasma deposition layer during the plasma deposition process, thereby improving the bonding effect between the graphene modified layer and the plasma deposition layer, and improving the bonding effect between the winding layer, the graphene modified layer and the deposition layer.
[0064] In one example, the carbon fiber composite material includes carbon fiber and resin matrix prepreg; the mass ratio of graphene to magnetic nanoparticles is 1:(0.1-2); the graphene and magnetic nanoparticles form a first mixed system, and the mass ratio of the first mixed system to the resin matrix prepreg is (0.1-5):100. The preparation method of the graphene modified layer is as follows:
[0065] Step 1), uniformly mixing graphene and magnetic nanoparticles according to the above mass ratio of 1: (0.1-2), so that the magnetic nanoparticles are adsorbed on the surface of the graphene to obtain magnetically modified modified graphene, and then adding the modified graphene to the resin matrix and uniformly mixing to obtain a resin matrix prepreg, wherein the mass ratio of the modified graphene to the resin matrix prepreg is (0.1-5): 100;
[0066] Step 2), arranging carbon fibers in parallel to form a carbon fiber bundle, pre-impregnating the carbon fiber bundle into the resin matrix prepreg obtained in S2, and then passing the pre-impregnated carbon fiber bundle through a magnetic field, so that under the action of the magnetic field, the graphene adsorbed with magnetic nanoparticles in the resin matrix prepreg pre-impregnated with the carbon fiber bundle is evenly arranged on the upper and lower sides of the carbon fiber bundle, and graphene modified layers are respectively formed on the upper and lower sides of the carbon fiber bundle, and finally a carbon fiber composite material is obtained;
[0067] Step 3), then wind the carbon fiber composite material to form a first winding layer 31, spray a plasma deposition layer on the outer surface of the first winding layer 31, and wind the second winding layer 32 on the outer surface of the plasma deposition layer, finally forming a graphene modified layer and a plasma deposition layer between the two winding layers.
[0068] Further, the mass ratio of the graphene to the magnetic nanoparticles is set to 1:(0.5-1.8); the graphene and the magnetic nanoparticles form a first mixed system, and the mass ratio of the first mixed system to the resin matrix prepreg is (0.5-4):100. Further, the mass ratio of the graphene to the magnetic nanoparticles is 1:(0.5-1.5); the graphene and the magnetic nanoparticles form a first mixed system, and the mass ratio of the first mixed system to the resin matrix prepreg is (0.5-3):100. When the content of the magnetic nanoparticles relative to the graphene is less, the degree of magnetic modification of the graphene is low. In the above step 2), through the action of the magnetic field, only the modified graphene is "attracted" to the upper side and / or lower side of the carbon fiber bundle, and the graphene that is not magnetically modified can only be left in the resin matrix, so that the graphene cannot be fully utilized. When the content of the magnetic nanoparticles relative to the graphene is more, the magnetic nanoparticles are easily accumulated into agglomerates, affecting the uniformity of the graphene modified layer.
[0069] In one example, the liner-free carbon fiber fully wound composite gas cylinder 1 further includes a second graphene modified layer disposed between the plasma deposited layer and the second wound layer; the second graphene modified layer is a layer structure formed by graphene with magnetic nanoparticles adsorbed on the surface. Specifically, the second graphene modified layer has the same structure as the first graphene modified layer, and the plasma deposited layer is sandwiched between the two, so that the plasma deposited layer is more tightly combined with the two adjacent wound layers.
[0070] In one example, the magnetic nanoparticles are Fe3O4 magnetic nanoparticles. Fe3O4 magnetic nanoparticles have strong magnetism, can maintain good magnetic properties even at high temperatures, have good dimensional stability, and are not easily affected by factors such as chemical corrosion, mechanical wear and thermal expansion.
[0071] In one example, the thickness ratio of the plasma deposited layer to the first winding layer is (0.1-2): 1. Further, the thickness ratio of the plasma deposited layer to the first winding layer 31 is (0.3-1.8): 1. Further, the thickness ratio of the plasma deposited layer to the first winding layer 31 is (0.5-1.5): 1. The plasma deposited layer has a high deposition density and can be used as a main anti-leakage layer.
[0072] The precursor materials of the plasma deposition layer include metal materials, ceramic materials and metal organics. Further, when the precursor material is a metal material, the metal material can be at least one material selected from Al, Fe, Ti, Co, Ni, Cu, Ru, Pd, Ag, Ta, Ir, Pt and their alloys, or other metal materials not mentioned, which are not limited here; when the precursor material is a ceramic material, the ceramic material can be at least one material selected from titanium nitride, zirconium nitride, zirconium carbide, zirconium carbonitride, titanium oxide, copper aluminum oxide, or other ceramic materials not mentioned, which are not limited here; when the precursor material is a metal organic, the metal organic can be at least one compound selected from metal alkyl compounds, metal cyclopentadienyl compounds, metal amide compounds and metal ether compounds, or other metal organics not mentioned, which are not limited here.
[0073] The embodiment of the present application also discloses a method for preparing the above-mentioned liner-free carbon fiber fully-wound composite material gas cylinder 1, comprising the following steps:
[0074] S1. A first mixed system: mixing graphene and magnetic nanoparticles so that the magnetic nanoparticles are adsorbed on the surface of the graphene to obtain the first mixed system;
[0075] The magnetic nanoparticles are Fe3O4 magnetic nanoparticles, and the mass ratio of graphene to magnetic nanoparticles is 1:(0.1-2);
[0076] S2. Resin matrix prepreg: The first mixed system obtained in S1 is added to the resin matrix and mixed evenly to obtain the resin matrix prepreg;
[0077] The mass ratio of the first mixed system to the resin matrix prepreg is (0.1-5):100;
[0078] S3. Carbon fiber composite material: several carbon fibers are arranged in parallel to form a carbon fiber bundle, the carbon fiber bundle is pre-impregnated into the resin matrix prepreg obtained in S2, and then the pre-impregnated carbon fiber bundle is passed through a magnetic field, under the action of the magnetic field, the graphene adsorbed with magnetic nanoparticles in the resin matrix prepreg pre-impregnated with the carbon fiber bundle is uniformly arranged on the upper and lower sides of the carbon fiber bundle, and graphene modified layers are respectively formed on the upper and lower sides of the carbon fiber bundle, and finally a carbon fiber composite material is obtained;
[0079] The prepreg temperature is 50°C-200°C, and the prepreg time is 1-5min; the magnetic field is a double-layer magnetic field, which is respectively arranged on the upper and lower sides of the carbon fiber bundle path, and the speed of the carbon fiber bundle passing through the magnetic field is 1-2m / min; the magnetic intensity of the double-layer magnetic field is the same, so that the structure of the graphene modified layer formed on the upper and lower sides of the carbon fiber bundle is the same;
[0080] S4. Central body: The carbon fiber composite material obtained in S3 is wound to form a first winding layer, a plasma deposition layer is sprayed on the outer surface of the first winding layer, and a second winding layer is wound on the outer surface of the plasma deposition layer to obtain the central body;
[0081] Wherein, the thickness ratio of the plasma deposited layer to the first winding layer is (0.1-2):1;
[0082] In one embodiment, the spraying temperature of the plasma deposited layer is not lower than the winding temperature of the first winding layer, and is not higher than the melting temperature of the resin matrix in the carbon fiber composite material. Generally, the temperature of the first winding layer is the temperature of the prepreg on the surface of the first winding layer. During the winding process, the prepreg on the surface of the winding layer is usually in a softened state.
[0083] In an optional embodiment, the plasma deposition layer is sprayed at low temperature, the spraying temperature is 20°C-60°C, the winding temperature of the first winding layer is room temperature, and the prepreg on the surface of the winding layer exceeds 60°C, the fluidity may become larger, increasing the uncertainty of the prepreg flow direction, and affecting the stability of the structure between layers. The precursor material of the low-temperature plasma deposition layer with a spraying temperature of 20°C-60°C can be a nitride (such as titanium nitride, zirconium nitride) or an oxide (such as titanium oxide).
[0084] In another optional embodiment, if the fluidity of the prepreg on the surface of the first winding layer is relatively high, the sprayed winding layer may be pre-cured before the plasma deposition layer is sprayed to reduce the fluidity of the prepreg on the surface of the sprayed winding layer.
[0085] The precursor materials of the plasma deposition layer include metal materials, ceramic materials and metal organics. Further, when the precursor material is a metal material, the metal material can be at least one material selected from Al, Fe, Ti, Co, Ni, Cu, Ru, Pd, Ag, Ta, Ir, Pt and their alloys, or other metal materials not mentioned, which are not limited here; when the precursor material is a ceramic material, the ceramic material can be at least one material selected from titanium nitride, zirconium nitride, zirconium carbide, zirconium carbonitride, titanium oxide, copper aluminum oxide, or other ceramic materials not mentioned, which are not limited here; when the precursor material is a metal organic, the metal organic can be at least one compound selected from metal alkyl compounds, metal cyclopentadienyl compounds, metal amide compounds and metal ether compounds, or other metal organics not mentioned, which are not limited here.
[0086] It should be noted that the resin matrix used in the "resin matrix prepreg" in this application can be a thermosetting resin matrix or a thermoplastic resin matrix. The resin in the thermosetting resin matrix, such as epoxy resin, phenolic resin, benzoxazine, bismaleimide, polyimide; the thermoplastic resin matrix, such as mainly polysulfone, polyphenylene sulfide, polyether sulfone and other resins, is not limited here.
[0087] It should be noted that the precursor material of the plasma deposition layer is appropriately selected according to the properties of the prepreg material on the surface of the sprayed winding layer.
[0088] The present application also provides the following embodiments:
[0089] Example 1 Preparation of Centrosome 1#
[0090] S1. A first mixed system: mixing graphene and magnetic nanoparticles so that the magnetic nanoparticles are adsorbed on the surface of the graphene to obtain the first mixed system;
[0091] The magnetic nanoparticles are Fe3O4 magnetic nanoparticles, and the mass ratio of graphene to magnetic nanoparticles is 1:0.5;
[0092] S2. Resin matrix prepreg: The first mixed system obtained in S1 is added to the resin matrix and mixed evenly to obtain the resin matrix prepreg;
[0093] The mass ratio of the first mixed system to the resin matrix prepreg is 0.5:100;
[0094] S3. Carbon fiber composite material: several carbon fibers are arranged in parallel to form a carbon fiber bundle, the carbon fiber bundle is pre-impregnated into the resin matrix prepreg obtained in S2, and then the pre-impregnated carbon fiber bundle is passed through a magnetic field, under the action of the magnetic field, the graphene adsorbed with magnetic nanoparticles in the resin matrix prepreg pre-impregnated with the carbon fiber bundle is uniformly arranged on the upper and lower sides of the carbon fiber bundle, and graphene modified layers are respectively formed on the upper and lower sides of the carbon fiber bundle, and finally a carbon fiber composite material is obtained;
[0095] The prepreg temperature is 80°C and the prepreg time is 2 minutes. The magnetic field is a double-layer magnetic field, which is respectively arranged on the upper and lower sides of the carbon fiber bundle path, and the speed of the carbon fiber bundle passing through the magnetic field is 2 m / min. The magnetic intensity of the double-layer magnetic field is the same, so that the structure of the graphene modified layer formed on the upper and lower sides of the carbon fiber bundle is the same.
[0096] S4. Central body: The carbon fiber composite material obtained in S3 is wound to form a first winding layer, a plasma deposition layer is sprayed on the outer surface of the first winding layer, a second winding layer is wound on the outer surface of the plasma deposition layer, and then other winding layers are wound to obtain the central body 1#;
[0097] Wherein, the thickness ratio of the plasma deposited layer to the first winding layer is 0.5:1;
[0098] It should be noted here that in step S4, a plasma deposition layer is only provided between adjacent winding layers, and a graphene modified layer is provided on the inner and outer sides of each winding layer in the adjacent winding layers, and no graphene modified layer is provided on other winding layers.
[0099] Example 2 Preparation of Centrosome 2#
[0100] S1. A first mixed system: mixing graphene and magnetic nanoparticles so that the magnetic nanoparticles are adsorbed on the surface of the graphene to obtain the first mixed system;
[0101] The magnetic nanoparticles are Fe3O4 magnetic nanoparticles, and the mass ratio of graphene to magnetic nanoparticles is 1:1;
[0102] S2. Resin matrix prepreg: The first mixed system obtained in S1 is added to the resin matrix and mixed evenly to obtain the resin matrix prepreg;
[0103] The mass ratio of the first mixed system to the resin matrix prepreg is 2:100;
[0104] S3. Carbon fiber composite material: several carbon fibers are arranged in parallel to form a carbon fiber bundle, the carbon fiber bundle is pre-impregnated into the resin matrix prepreg obtained in S2, and then the pre-impregnated carbon fiber bundle is passed through a magnetic field, under the action of the magnetic field, the graphene adsorbed with magnetic nanoparticles in the resin matrix prepreg pre-impregnated with the carbon fiber bundle is uniformly arranged on the upper and lower sides of the carbon fiber bundle, and graphene modified layers are respectively formed on the upper and lower sides of the carbon fiber bundle, and finally a carbon fiber composite material is obtained;
[0105] The prepreg temperature is 120°C, and the prepreg time is 2 minutes. The magnetic field is a double-layer magnetic field, which is respectively arranged on the upper and lower sides of the carbon fiber bundle path, and the speed of the carbon fiber bundle passing through the magnetic field is 2 m / min. The magnetic intensity of the double-layer magnetic field is the same, so that the structure of the graphene modified layer formed on the upper and lower sides of the carbon fiber bundle is the same.
[0106] S4. Central body: The carbon fiber composite material obtained in S3 is wound to form a first winding layer, a plasma deposition layer is sprayed on the outer surface of the first winding layer, a second winding layer is wound on the outer surface of the plasma deposition layer, and then other winding layers are wound to obtain the central body 2#;
[0107] Wherein, the thickness ratio of the plasma deposited layer to the first winding layer is 1:1;
[0108] It should be noted here that in step S4, a plasma deposition layer is only provided between adjacent winding layers, and a graphene modified layer is provided on the inner and outer sides of each winding layer in the adjacent winding layers, and no graphene modified layer is provided on other winding layers.
[0109] Example 3 Preparation of Centrosome 3#
[0110] S1. A first mixed system: mixing graphene and magnetic nanoparticles so that the magnetic nanoparticles are adsorbed on the surface of the graphene to obtain the first mixed system;
[0111] The magnetic nanoparticles are Fe3O4 magnetic nanoparticles, and the mass ratio of graphene to magnetic nanoparticles is 1:1.8;
[0112] S2. Resin matrix prepreg: The first mixed system obtained in S1 is added to the resin matrix and mixed evenly to obtain the resin matrix prepreg;
[0113] The mass ratio of the first mixed system to the resin matrix prepreg is 4:100;
[0114] S3. Carbon fiber composite material: several carbon fibers are arranged in parallel to form a carbon fiber bundle, the carbon fiber bundle is pre-impregnated into the resin matrix prepreg obtained in S2, and then the pre-impregnated carbon fiber bundle is passed through a magnetic field, under the action of the magnetic field, the graphene adsorbed with magnetic nanoparticles in the resin matrix prepreg pre-impregnated with the carbon fiber bundle is uniformly arranged on the upper and lower sides of the carbon fiber bundle, and graphene modified layers are respectively formed on the upper and lower sides of the carbon fiber bundle, and finally a carbon fiber composite material is obtained;
[0115] The prepreg temperature is 180°C, and the prepreg time is 2 minutes. The magnetic field is a double-layer magnetic field, which is respectively arranged on the upper and lower sides of the carbon fiber bundle path, and the speed of the carbon fiber bundle passing through the magnetic field is 2 m / min. The magnetic intensity of the double-layer magnetic field is the same, so that the structure of the graphene modified layer formed on the upper and lower sides of the carbon fiber bundle is the same.
[0116] S4. Central body: The carbon fiber composite material obtained in S3 is wound to form a first winding layer, a plasma deposition layer is sprayed on the outer surface of the first winding layer, a second winding layer is wound on the outer surface of the plasma deposition layer, and then other winding layers are wound to obtain the central body 3#;
[0117] Wherein, the thickness ratio of the plasma deposited layer to the first winding layer is 1:1;
[0118] It should be noted here that in step S4, a plasma deposition layer is only provided between adjacent winding layers, and a graphene modified layer is provided on the inner and outer sides of each winding layer in the adjacent winding layers, and no graphene modified layer is provided on other winding layers.
[0119] Comparative Example 1 Preparation of Comparative Centrosome 1'#
[0120] Different from the preparation method of Example 2, the first mixed system formed by mixing graphene and magnetic nanoparticles is not added to the resin matrix prepreg in S2. Finally, the comparative central body 1'# is obtained. Compared with the central body 2#, the comparative central body 1'# does not have a graphene modified layer.
[0121] Comparative Example 2 Preparation of Comparative Centrosome 2'#
[0122] The difference from the preparation method of Example 2 is that in S4, the plasma deposition layer is not sprayed. Finally, the comparative central body 2'# is obtained. Compared with the central body 2#, the comparative central body 2'# is not provided with a plasma deposition layer.
[0123] Comparative Example 3 Preparation of Comparative Centrosome 3'#
[0124] Different from the preparation method of Example 2, the first mixed system formed by mixing graphene and magnetic nanoparticles is not added to the resin matrix prepreg in S2; and the plasma deposition layer is not sprayed in S4. Finally, the comparative central body 3'# is obtained. Compared with the central body 2#, the comparative central body 3'# does not have a graphene modified layer and a plasma deposition layer.
[0125] Example 4 Testing the gas permeability of central bodies 1#-3# and comparative central bodies 1'#-3'#
[0126] The hydrogen permeation test is carried out at (15±1)℃ and 0.1 times the nominal working pressure using the method specified in GB / T 42610 (6.1.2 Hydrogen permeation test). Qualified indicators: No bubbles on the surface of the sample, and the hydrogen permeability coefficient should be less than or equal to 9.0×10 -16 mo lm / (m 2 .s.Pa)
[0127] Samples were taken from each center body 1#-3# and comparison center body 1'#-3'#, specifically, 12 hydrogen permeation samples were taken from each center body, divided into three groups, 4 samples in each group. Before the test, the samples were placed in a vacuum drying oven with an absolute pressure of 1000Pa-5000Pa and a temperature of 65°C until the mass loss of the samples within 24 hours was less than 0.1%.
[0128] The test results are shown in Table 1 below:
[0129] Table 1
[0130]
[0131]
[0132] From the test results in Table 1, it can be seen that the central bodies 1#-3# are all provided with graphene modification layers and plasma deposition layers, there is no bubbling on the surface, and the hydrogen permeability coefficient is less than 9.0×10 -16 mo lm / (m 2 .s.Pa), all of which are qualified. In contrast, the central body 1'# has no graphene modification layer compared to the central body 2#, and a few bubbles appear on the surface of the sample, and the hydrogen permeability coefficient is greater than 9.0×10 -16 mo lm / (m 2 .s.Pa); Compared with the central body 2#, the central body 2'# does not have a dense plasma deposition layer, and a few bubbles appear on the surface of the sample, and the hydrogen permeability coefficient is also greater than 9.0×10 -16 mo lm / (m 2.s.Pa); Compared with the central body 2#, the central body 3'# has neither a graphene modified layer nor a plasma deposition layer. A large number of bubbles appear on the surface of the sample, and the hydrogen permeability coefficient is the largest. This shows that adding both the graphene modified layer and the plasma deposition layer can effectively improve the anti-permeability performance of the unlined carbon fiber fully wrapped composite gas cylinder.
[0133] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A liner-free carbon fiber fully wound composite gas cylinder, comprising a central body, wherein the central body comprises a multi-layer structure and a gas storage cavity surrounded by the multi-layer structure, characterized in that: The multi-layer structure comprises: A plurality of composite carbon fiber winding layers, which are formed by winding carbon fiber composite materials; Wherein, at least one adjacent composite carbon fiber winding layer comprises a first winding layer and a second winding layer, and a first graphene modified layer and a plasma deposition layer are sequentially arranged from the outer side of the first winding layer to the inner side of the second winding layer; The first graphene modified layer is a layer structure formed by graphene with magnetic nanoparticles adsorbed on the surface; The carbon fiber composite material comprises carbon fiber and resin matrix prepreg; The mass ratio of the graphene to the magnetic nanoparticles is 1:(0.1-2); The graphene and the magnetic nanoparticles form a first mixed system, and the mass ratio of the first mixed system to the resin matrix prepreg is (0.1-5):100; Also comprising a second graphene modified layer disposed between the plasma deposited layer and the second winding layer; The second graphene modified layer is a layer structure formed by graphene with magnetic nanoparticles adsorbed on the surface.
2. The liner-free carbon fiber fully wound composite material gas cylinder according to claim 1, characterized in that: The magnetic nanoparticles are Fe3O4 magnetic nanoparticles.
3. The liner-free carbon fiber fully wound composite material gas cylinder according to claim 1, characterized in that: The thickness ratio of the plasma deposited layer to the first winding layer is (0.1-2):
1.
4. The liner-free carbon fiber fully wound composite material gas cylinder according to claim 1, characterized in that: The precursor materials of the plasma deposition layer include metal materials, ceramic materials and metal organics.
5. The liner-free carbon fiber fully wound composite material gas cylinder according to claim 4, characterized in that: The metal material includes at least one of Al, Fe, Ti, Co, Ni, Cu, Ru, Pd, Ag, Ta, Ir, Pt and alloys thereof; the ceramic material includes at least one of titanium nitride, zirconium nitride, zirconium carbide, zirconium carbonitride, titanium oxide and copper aluminum oxide; the metal organic compound includes at least one of metal alkyl compounds, metal cyclopentadienyl compounds, metal amide compounds and metal ether-based compounds.
6. A method for preparing a liner-free carbon fiber fully wound composite material gas cylinder, characterized in that: The preparation method comprises the following steps: S1. A first mixed system: mixing graphene and magnetic nanoparticles so that the magnetic nanoparticles are adsorbed on the surface of the graphene to obtain the first mixed system; S2. Resin matrix prepreg: The first mixed system obtained in S1 is added to the resin matrix and mixed evenly to obtain the resin matrix prepreg; S3. Carbon fiber composite material: several carbon fibers are arranged in parallel to form a carbon fiber bundle, the carbon fiber bundle is pre-impregnated into the resin matrix prepreg obtained in S2, and then the pre-impregnated carbon fiber bundle is passed through a magnetic field, under the action of the magnetic field, the graphene adsorbed with magnetic nanoparticles in the resin matrix prepreg pre-impregnated with the carbon fiber bundle is uniformly arranged on the upper and lower sides of the carbon fiber bundle, and graphene modified layers are respectively formed on the upper and lower sides of the carbon fiber bundle, and finally a carbon fiber composite material is obtained; S4. Central body: Winding the carbon fiber composite material obtained in S3 to first form a first winding layer, spraying a plasma deposition layer on the outer surface of the first winding layer, and winding a second winding layer on the outer surface of the plasma deposition layer to obtain the central body.
7. The preparation method according to claim 6, characterized in that: In S1, the magnetic nanoparticles are Fe3O4 magnetic nanoparticles, and the mass ratio of the graphene to the magnetic nanoparticles is 1:(0.1-2); In S2, the mass ratio of the first mixed system to the resin matrix prepreg is (0.1-5):100; In S3, the prepreg temperature is 50°C-200°C, and the prepreg time is 1-5 min; The magnetic field is a double-layer magnetic field, which is respectively arranged on the upper and lower sides of the path of the carbon fiber bundle, and the speed of the carbon fiber bundle passing through the magnetic field is 1-2m / min.
8. The preparation method according to claim 6, characterized in that: The spraying temperature of the plasma deposited layer is not lower than the temperature of the first winding layer, and is not higher than the molten state temperature of the resin matrix in the carbon fiber composite material.
9. The preparation method according to claim 7, characterized in that: The thickness ratio of the plasma deposited layer to the first winding layer is (0.1-2):1.
Citation Information
Patent Citations
Resin system used in ultralow-temperature liquid hydrogen environment and preparation method thereof
CN117736551A
Low-leakage storage tank based on interface sealing and manufacturing method thereof
CN117754902A
Lining-free fiber composite material gas cylinder suitable for ultralow-temperature liquid hydrogen environment and preparation method of lining-free fiber composite material gas cylinder
CN118110913A